2021
DOI: 10.1002/est2.287
|View full text |Cite
|
Sign up to set email alerts
|

Simplified photogalvanic cell design with promise for the enhanced solar electricity generation and storage

Abstract: Photogalvanicists have conventionally used complicated, multichambered, sophisticated, and very costly cell designs for solar electricity and storage. We authors have simplified cell design with encouraging electrical output as well.We authors have used a simple, cheap, and one-chambered cell design based on cylindrical glass tubes instead of the costly, conventional, and complex Hshaped glass tube-based cell fabrication design. The study has been done under similar electrolytic and illuminating conditions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 58 publications
1
5
1
Order By: Relevance
“…In the present study, the authors have also used a simple cylindrical glass vessel (relatively less D L ) for fabrication of the cell based on tropaeline‐O dye sensitizer (MW 316.27, azo dye with –SO 2 O − Na + and –OH groups), and have observed enhanced electrical output consistent with the reported study. However, the power output (power 829.5 μW, current 3200 μA) of the present study is relatively higher than that of the study reported (power 439 μW, current 2100 μA) 42 . The nature of the dye sensitizer is the main constituent influencing the electrical output of the PG cell.…”
Section: Comparison Of Results Of the Tropaelime‐o Dye Sensitizer Wit...contrasting
confidence: 80%
See 4 more Smart Citations
“…In the present study, the authors have also used a simple cylindrical glass vessel (relatively less D L ) for fabrication of the cell based on tropaeline‐O dye sensitizer (MW 316.27, azo dye with –SO 2 O − Na + and –OH groups), and have observed enhanced electrical output consistent with the reported study. However, the power output (power 829.5 μW, current 3200 μA) of the present study is relatively higher than that of the study reported (power 439 μW, current 2100 μA) 42 . The nature of the dye sensitizer is the main constituent influencing the electrical output of the PG cell.…”
Section: Comparison Of Results Of the Tropaelime‐o Dye Sensitizer Wit...contrasting
confidence: 80%
“…Conventionally, the H‐shaped glass tubes have been used to fabricate the PG cell. But, the recent study reported by Koli et al on Congo Red dye sensitizer (MW 696.66, a diazo dye with –SO 2 O − Na + and –NH 2 groups) has shown that the use of simple cylindrical glass vessels is not only cheap but also more efficacious in power generation 42 …”
Section: Comparison Of Results Of the Tropaelime‐o Dye Sensitizer Wit...mentioning
confidence: 99%
See 3 more Smart Citations